2017
DOI: 10.1590/0100-29452017403
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Area Estimation in Litchi by Means of Allometric Relationships

Abstract: ABSTRACT-Obtaining leaf area is critical in several agronomic studies, being one of the important instruments to assess plant growth. The aim of this study was to estimate equations and select the most appropriate in determining leaf area in litchi (Litchi chinensis Sonn.). From the linear dimensions of length (L) and maximum width (W) of leaf limb, equations were estimated using linear, quadratic, potential and exponential models. The linear regression equation using the product of the length by maximum width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 9 publications
0
19
1
4
Order By: Relevance
“…The use of regression models has become a very precise non-destructive method that allows the real leaf area of plants to be estimated from linear measurements of leaf blades (length and width), which are directly correlated with leaf surface area (ZHANG; PAN, 2011). Such methods have been used to estimate leaf area of both cultivated (GANESHAMURTHY et al, 2016;CARVALHO et al, 2017;OLIVEIRA et al, 2017) and forest species (ASSIS et al, 2015;KERAMATLOU et al, 2015;RIBEIRO et al, 2018b;RIBEIRO et al, 2019a;RIBEIRO et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The use of regression models has become a very precise non-destructive method that allows the real leaf area of plants to be estimated from linear measurements of leaf blades (length and width), which are directly correlated with leaf surface area (ZHANG; PAN, 2011). Such methods have been used to estimate leaf area of both cultivated (GANESHAMURTHY et al, 2016;CARVALHO et al, 2017;OLIVEIRA et al, 2017) and forest species (ASSIS et al, 2015;KERAMATLOU et al, 2015;RIBEIRO et al, 2018b;RIBEIRO et al, 2019a;RIBEIRO et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The region is characterized by tropical AW (tropical humid) climate, with rainfall in summer and dry winter according to the classification of köppen [15]. 500 leaves of 12 different plants were counted, and in each sampled plant, leaves were collected at all stages of development at the four cardinal points, which did not present damage or attack of diseases or pests, as suggested by Oliveira et al [13]. The leaves were packed in plastic bags and transported to the Plant Improvement Laboratory of the University of Espírito Santo (CEUNES).…”
Section: Methodsmentioning
confidence: 99%
“…[8], Vitis vinífera L. [10], Coffea canephora [9], Crotalaria juncea [5], Litchi chinensis Sonn. [13], Prunus armeniaca L. [14] and Annona cherimila Mill. [12] indicated that the product of the combination of length and width is more predictive in estimating the leaf area of these species.…”
Section: Ssionmentioning
confidence: 99%
“…Note in Figure 3 that models involving a single measurement were less acceptable in the C. rosea leaf area estimate due to its lower R 2 values. In addition, the equations based on L and W individually presented MAE and RMSE values that were farther from zero and values of the Willmott d index more distinct to one, when compared the models using LW (Table 3), these criteria should be used to select the model that best fits the leaf area estimate (Oliveira et al, 2017). It was also verified that the comparative means of OLA and ELA did not statistically differ by Student's t test at 5% of probability in all proposed models (Table 3), attesting a good similarity of the means of OLA and ELA.…”
Section: Methodsmentioning
confidence: 99%
“…In this way, are notorious the great number of works involving mathematical equations as non-destructive method to estimate the leaf area in a wide range of vegetal species as Cucumis sativus L. (Cho, S. Oh, M. M. Oh, & Son, 2007), Helianthus annuus L. (Rouphael, Colla, Fanasca, & Karam, 2007), Jatropha curcas (Pompelli et al, 2012), Vitis vinífera L. (Buttaro, Rouphael, Rivera, Colla, & Gonnella, 2015), Coffea canephora (Schmildt, Amaral, Santos, & Schmildt, 2015), Rosa hybrida L. (Costa, Pôças, & Cunha, 2016), Crotalaria juncea (Carvalho et al, 2017), Prunus armeniaca L. (Cirillo et al, 2017), Litchi chinensis Sonn (Oliveira, Silva, Costa, Schmildt, & Vitória, 2017), guava (Vitória et al, 2018), Carica papaya L. (Oliveira et al, 2019) and Plectranthus barbatus Andrews (Ribeiro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%